Kajian Kerjasama Multipihak dalam Penyuluhan Hortikultura (Bawang Merah) di Sepanjang Aktivitas Rantai Nilai di Kecamatan Lembah Gumanti Kabupaten Solok : Study of Multi-Stakeholders Cooperation in Horticultural Extension (Shallot) along the Value Chain Activities in Lembah Gumanti District Solok Regency - Virra Putri Silviana; Helmi; Rafnel (Research and Social Study Institute (RESSI), 2022)
This study aims to describe the implementation of extension and multi-stakeholder cooperation and identify the forms of extension and multi-stakeholder cooperation needed along the shallot value chain activities. This research usesd qualitative method with puposive sampling techniques with certain considerations.Tthe samples consisted of farmers, private extension agent, self-help extension agent, government extension agent, and shallot trader. The result showed that the implementationof extension activities along the shallot value chain activities was still limited, which is still focused on the aspect of pre-production and production only. Extension activities needed are activities that can provide solutions to every problem by farmers, from pre-production to distribution. Multi-stakeholders cooperation and collaboration extension along the activites of the value chain are needed to advance current agriculture. All categories of agricultural extension agent and the government must form cooperation in providing support related to extension activities along the value chain so that farmer’s production (shallot supply to the market) and prices become stable. Multistakeholders cooperation that can be done is to utilize the potential and information possessed by all parties concerned and create a digital platform that serves to support the extension activities along the value chain activities (integrating production and marketing and synergizing extension workers.